2009
DOI: 10.1017/s1368980008002413
|View full text |Cite
|
Sign up to set email alerts
|

Intake of B vitamins in childhood and adult life in relation to psychological distress among women in a British birth cohort

Abstract: Background: Lower levels of B vitamins (particularly folate, vitamin B 12 and vitamin B 6 ) may be associated with psychological distress. Little is known about the impact of childhood nutrition on psychological distress in adult life. Objective: We investigated whether prospectively measured childhood and adult dietary intakes of thiamin, riboflavin, niacin, folate, vitamin B 6 and vitamin B 12 were related to the psychological distress of women in mid-age, taking into account socio-economic, behavioural and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…Some studies describing the relationship between diet and mental health already exist [15][16][17][18][19]. Jacka et al reported that the intake of magnesium, folate, and zinc was associated with mental health using the validated food frequency questionnaire and the GHQ-12 [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies describing the relationship between diet and mental health already exist [15][16][17][18][19]. Jacka et al reported that the intake of magnesium, folate, and zinc was associated with mental health using the validated food frequency questionnaire and the GHQ-12 [15].…”
Section: Discussionmentioning
confidence: 99%
“…Jacka et al reported that the intake of magnesium, folate, and zinc was associated with mental health using the validated food frequency questionnaire and the GHQ-12 [15]. Mishra et al showed that low dietary vitamin B 12 intake was also associated with higher psychological distress [16]. In Japan, Miki et al reported that the intake of magnesium, calcium, iron, and zinc was negatively correlated with symptoms of depression [17].…”
Section: Discussionmentioning
confidence: 99%
“…The Panel considers that evidence from only one observational study on a particular outcome is not sufficient to provide strong evidence of a relationship and thus cannot be used for setting DRVs for riboflavin. Thus, data on riboflavin intake and bone mineral density in postmenopausal women (Rejnmark et al, 2008), the risk of overactive bladder syndrome (Dallosso et al, 2004), the risk of premenstrual syndrome (Chocano-Bedoya et al, 2011), 'psychological distress' (Mishra et al, 2009), cognition (La Rue et al, 1997, risk of total cardiovascular diseases (Zee et al, 2007), or cancer at some sites (gastric adenocarcinoma (Eussen et al, 2010); pancreatic cancer (Chuang et al, 2011); prostate cancer (Bassett et al, 2012a); oral carcinoma (Petridou et al, 2002); ovarian cancer (Kabat et al, 2008); oesophageal cancer (Siassi et al, 2000); cervical cancer (Liu et al, 1993); renal cell carcinoma (Gibson et al, 2010)) are not considered below. In addition, intervention studies investigating riboflavin supplementation, in addition to intake, at levels higher than the observed average intake of riboflavin in the EU (Appendices C and D) were also not considered by the Panel in this Section (e.g.…”
Section: 3mentioning
confidence: 99%
“…Many studies concerning effects of specific nutrients, food types and eating patterns on brain function have been conducted, and several mental health conditions appear to have received significant attention in terms of diet and nutrition including depression, bipolar disorder and schizophrenia, as well as attention deficit hyperactive disorder (ADHD) and behavioural problems, such as aggressive and violent behaviour (e.g. Jacka et al, 2009;Mishra, McNaughton, O'Connell, Prynne, and Kuh 2009;Montgomery & Richardson, 2008;Schnoll, Burshteyn, & Cea-Aravena, 2003;Zaalberg, Nijman, Bulten, Luwe, & van der Staak, 2010). Biochemical imbalances, such as dysglycaemia (fluctuating blood sugar), are highlighted as producing a range of mental and emotional disturbance, for example anxiety, mood swings, depression and forgetfulness (Food for the Brain, 2015).…”
Section: Introductionmentioning
confidence: 99%